Perawatan Fraktur Kelas Tiga Ellis pada Gigi Tetap Insisif Sentral Atas - Eva Fauziah; Hendrarlin Soenawan (Faculty of Dentistry, Universitas Indonesia, 2013)
The anterior teeth have the essential esthetics function , so when the trauma occur, the immediately treatment must be done to avoid its dysfunction. Andreas Jo reported in 1984 that 18 percent to 20 percent of traumatic injury in young permanent teeth caused the crown fractures with exposed pulps. This traumatic injury must be managed correctly to keep the pulp normal. Accurate examination and anamnesis must be done before treatment. The prompt treatment to relieve pain, to cover pulps from irritating material and maintain pulp vitality is neededOne alternative treatment for crown fracture with exposed pulp in young permanent is by using pulpotomy with calcium hydroxide. The function of calcium hydroxide is to maintain pulp vitality and stimulate reparative dentin and close the apex. Then, glass ionomer cement is used to support the pulp cap and then resin composite as temporary restoration to recover the function of mastication and esthetics, until the permanent restoration is made. In this case, ,the radiographic showed reparative dentin after four weeks of pulpotomy calcium hydroxide applied. So there was the fact that it took six month to make the apex is close from the beginning of treatment. DOI: 10.14693/jdi.v15i2.75